ANALISIS PERBANDINGAN TINGKAT KEBISINGAN LALU LINTAS MENGGUNAKAN METODE CORTN DAN METODE SNI 8427:2017 (STUDI KASUS: SEGMEN JALAN SULTAN HASANUDDIN KABUPATEN GOWA) - Chandra, Hendrawan; Thioritz, Stevy; Kalangi, Hendry Tanoto (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Atma Jaya Makassar, 2024)
Noise is one form of pollution that disrupts the quality of human life, on Jalan Sultan Hasanuddin Gowa Regency, the location to be studied is very high traffic activity makes the area along the trade area becomes very noisy. This study aims to analyze the noise level in the trade area using two methods, namely the CoRTN method (1 hour and 18 hours) and SNI 8427: 2017 (1 hour and 18 hours) and compare the results with the quality standards allowed in the trade area. Based on the research results, the highest noise level of the CoRTN method for 1 hour was recorded on Saturday at 14.00-15.00 WITA at 77.36 dB(A), while the SNI 8427:2017 method on Friday at 22.00-23.00 WITA reached 82.63 dB(A). Based on the results of the 18-hour study, the highest noise level of the CoRTN method was recorded on Saturday at 76.61 dB(A), while the SNI 8427:2017 method reached 81.40 dB(A). According to the Decree of the Minister of Environment No. 48 Year 1996 on the noise quality standard in trading areas of 70 dB(A), the results of this study show that the noise level exceeds the permitted quality standard.